Answer:
x = 6
y = 2
Explanation:
Solve for x in the first equation:
-5x + 4y = -22
Step 1 - Subtract 4y from both sides:
-5x + 4y - 4y = -22 - 4y
-5x = -22 - 4y
Step 2 - Change every operation to its opposite counterpart:
5x = 22 + 4y
Divide both sides by 5:
![(5x)/(5) =( (22 + 4y) )/(5)](https://img.qammunity.org/2022/formulas/mathematics/college/32fax1b7w1zov5ztm8kxprao2aketn2m0c.png)
![x = ( (22 + 4y) )/(5)](https://img.qammunity.org/2022/formulas/mathematics/college/e9l6bv7h28p8p12xepmydeckjjfxy768n3.png)
Step 3 - Now substitute this into the second equation:
-3x - 4y = -26
-3(
) - 4y = -26
-3(
)
![(-3)/(1) * (1)/(5) = (-3)/(5)](https://img.qammunity.org/2022/formulas/mathematics/college/h4xtpayimyla3equl119vfay9ibi62llcg.png)
![(-3)/(5)(22 + 4y) - 4y = -26](https://img.qammunity.org/2022/formulas/mathematics/college/um7t0himgkoqlgx8qvzbdpm3ygyfj33g2z.png)
Step 4 - Multiply both sides by 5:
![-3(22 + 4y) - 5(4y) = -(5)26\\-3(22 + 4y) - 20y = -130](https://img.qammunity.org/2022/formulas/mathematics/college/hkrg1d3sdpj0ncp6apfs73jn801zg06g7k.png)
Step 5 - Simplify the brackets
![-66 -12y - 20y = -130](https://img.qammunity.org/2022/formulas/mathematics/college/fw0bvr9b5eqfn4tc12x9f6dzro27h4drsh.png)
130 = 66 + 12y + 20y
130 = 66 + 32y
Step 6 - Subtract 66 from both sides of the equation;
130 - 66 = 66 + 32y - 66
64 = 32y
Step 7 - Divide both sides by 32:
![(64)/(32) = (32y)/(32)](https://img.qammunity.org/2022/formulas/mathematics/college/ramcguvxvj2b9t1j0u64wak9al4fpxp0am.png)
2 = y
Step 8 - So y = 2, so now we can substitute this into one of the equations:
-5x + 4y = -22
-5x + 4(2) = -22
-5x + 8 = -22
Subtract 8 from both sides
-5x + 8 - 8 = -22 - 8
-5x = -30
5x = 30
Divide both sides by 5:
![(5x)/(5) = (30)/(5)](https://img.qammunity.org/2022/formulas/mathematics/college/6gc1bioxztqmunxxhmce5ie4qjislf1dny.png)
x = 6
Hope this helps!